STEREOTYPE TO PUNK IN THE SONG’S LYRICS OF AMERICAN IDIOT ALBUM BY GREEN DAY - Daffa, Brian (Prologue: Journal on Language and Literature, 2025)
This research aims to analyse the stereotype to punk in the song’s lyrics of American idiot album by green day, the objective of this research is to identify the stereotype in the song’s lyrics. The theory used in this research is semiotic by Michael Riffaterre specifically semiotic poetry’s heuristic and hermeneutic reading. The method used in this research is qualitative in descriptive way. The researcher found there are negative and positive stereotype to punk in the song’s lyrics, the negative stereotypes are rebellious, violent and drug/alcohol addict. The positive stereotype is free/independent, The research show that there is more negative stereotype than positive stereotype in the song’s lyrics with the stereotype form, negative stereotype has a negative outcome and positive stereotype has a positive outcome for the character.